Matching worker skills to job tasks in the Netherlands: Sorting into cities for better careers - Suzanne Kok (IZA Journal of European Labor Studies, 2014)
Matches between workers and jobs are better in thick labour markets than in thin ones. This paper measures match quality by the gap between worker skills and their job tasks in the Netherlands. The smaller the gap, the better the match between skills and tasks. The measured gaps are 14 percent of a standard deviation smaller in cities than in the Dutch countryside. The location of work explains the observed higher quality of matches, while the location of residence does not. Robustness analyses show that these results are not explained by more efficient learning in cities or the spatial distribution of industrial and service occupations. Higher matching quality is associated with higher wages and explains part of the urban wage premia.
Keywords: J24; J23; R12; R23; 330; Matching; Skills; Tasks; Cities